2019
DOI: 10.1186/s13019-019-0925-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of trans-thoracic echocardiography and coronary CT angiography to diagnose mitral valve prolapse

Abstract: Objective At present, multi-detector cardiac CT has been widely applied in the detection of heart valve morphology and function. This study aims to compare the coronary CT angiography and trans-thoracic echocardiography for patients with mitral valve prolapse. Methods CT angiography and trans-thoracic echocardiography were adopted to detect the movement range and thickness of valvula bicuspidalis. The ultrasonic parameters of CT angiography were considered as standard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…17 Some studies have shown that CTA has better accuracy and reliability than TTE in diagnosing mitral valve prolapse. 18 The importance of CTA evaluation of the mitral valve is essential when evaluating patients for transcatheter mitral valve replacement.…”
Section: Pathophysiology and Classificationmentioning
confidence: 99%
“…17 Some studies have shown that CTA has better accuracy and reliability than TTE in diagnosing mitral valve prolapse. 18 The importance of CTA evaluation of the mitral valve is essential when evaluating patients for transcatheter mitral valve replacement.…”
Section: Pathophysiology and Classificationmentioning
confidence: 99%